The Intersection between Artificial Intelligence, Interdisciplinary Collaboration and African History - Esamagu, Efemena Emmanuel; Wazhi, Emmanuel Nimnan; Adeyinka , Taiwo Adebayo (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
This paper basically considered the effects of AI on African history, vis-à-vis interdisciplinary collaboration, either overtly or covertly. It posited that recent historical works embrace interdisciplinary perspective, thus, it was examined in light of the emergence of AI. Being a historical piece of work, historical methodology was adopted as secondary sources in this case, which consist of published and unpublished works. These formed the gamut of data collection used to prosecute and enrich this research. The paper sought to answer the following questions: what is the connection between artificial intelligence, interdisciplinary collaboration and African history? What are the effects of AI on African history as a specialization? The core of the paper is necessitated by the emergence of AI. As such, it was juxtaposed vis-a-vis African history and other related disciplines. On the whole, the study established or found out that artificial intelligence (AI), though with its negative impact, has enhanced and strengthened new trends and perspectives in African historical research vis-à-vis the relationships between History, Social and Natural Sciences; History, Sociology and Anthropology; History and Psychology; History, Economics and Demographic Studies; History and Literature; which was exhaustively explained in the paper. While the paper noted that AI, when used properly, could provide relevant information critical to historical studies. It also highlighted the challenges which stem from the use of artificial intelligence, which include: data bias and representation, contextual understanding, source reliability and verification, ethical considerations, complexity of interpretation, technical limitations, preservation of historical integrity, among others. The study concluded that historians generally, and African historians in particular exercised caution in the use of AI for comprehensive historical research.